THE USE OF PICTURE BOOK TO IMPROVE STUDENTS’ READING SKILL AT MTS MA’ARIF NU - Risda Dameiyanti (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This research aims to explain the benefits of picture book as an alternative learning for students in particular and society in general to improve the knowledge of its readers. The basic foundation of researchers conducting this research is because most students are not interested in reading. This happens because the book form is thick, boring and unattractive. To overcome the problem is by way of media books that can attract the attention of reading. Such as picture book.The purpose of this study was to find out whether the use of picture books in teaching English improves reading comprehension of second-year students of MTU Ma'arif NU. The research design of this study was classroom action research (CAR) conducted in one cycle consisting of four meetings. The researcher was limited to the second year students of MTs Ma'arif NU which consisted of 34 students. In this study researchers used several instruments; namely: field notes to retrieve information on student activities in class and reading tests to determine student achievement.The researcher making list several criteria for students' success in learning reading using picture book. The criteria for success should be set to determine whether the media successful or not. In this case, the study should be successful when 50% of students get a score 75 above. If it is not successful the researcher should do the second cycle and soon. It meant that the indicator of success is >75 in the student's score. To determine students' success, she or he could answer the test from the researcher based on the material.The research findings show that the application of picture books has improved students' reading comprehension; students become more motivated in reading, students get better scores in reading. That is evidenced by the average score of the cycle is 77.7. That is higher than the average score of the preliminary study, which is 61. 5 which means that students have improved their reading comprehension and achieved success criteria.This research discusses the use of picture books in improving students' reading skills.Before conducting research, the reading skills of students in second grade MTs Ma'arif NU were not good. They find difficulty in understanding the text. These factors come from low motivation, mastery of vocabulary, and background knowledge of students. There is no technique in teaching reading which also influences students' reading comprehension abilities. Students also do not know the important information needed to understand a word. In this connection, he hopes that this research can encourage principals to issue policies that provide opportunities for teachers to apply picture book learning and to develop alternative methods to make teaching and learning fun and effective. For further researchers, it is recommended to do other research on the same topic and use it as a reference.Key words: reading, picturebooks, less interested, and classroom action research.